FRI0340 Prevalence and significance of thrombocytopenia in juvenile-onset systemic lupus erythematosus at presentation and one year follow-up. (23rd January 2014) - Gohar, F.; Watson, L.; Beresford, M.W.
Abstract : Background: Thrombocytopenia is both common in adult-onset Systemic Lupus Erythematosus (SLE), prevalence ranging up to 40% and associated with increased disease activity, damage accrual and mortality (1). In juvenile-onset SLE (JSLE) thrombocytopenia appears more prevalent, but figures vary greatly by study. Thrombocytopenia is an independent risk factor for increased renal and neurological disease activity; both are more frequent in JSLE (2). In addition, thrombocytopenia can evolve from idiopathic thrombocytopenic purpura in a sub-set of patients to fulfil a JSLE diagnosis (3). Objectives: To establish 1) the prevalence of thrombocytopenia (TCP) in JSLE patients at baseline (T0) and one year post diagnosis (T12) and 2) any associations of TCP with: disease activity; laboratory markers and disease-related damage. Methods: A retrospective review of the UK national, multicentre JSLE inception Cohort Study & database was performed. Full ethical approval was in place. Patients were recruited between 2004 and 2011 and fulfilled at least four American College of Rheumatology (ACR) criteria for diagnosis at T0. Demographics, disease activity, laboratory results and damage accrual data was analysed at T0 and T12 (range 9-15mth). TCP was defined as <150, 000 platelets/mm 3, as per the British Isles Lupus Assessment Group (BILAG)-2004 definitions. Results are presented as median (range). Results: One hundred and fifty-five patients (83% female; age at diagnosis: 12.6 (1.8-17.9) years) were analysed, 27 (19%) of which had TCP at T0 (89×10 9 /L, 6-147) and 6 (4) at T12 (94×10 9 /L, 31-142). Two patients were thrombocytopenic at both T0 and T12. Significant TCP (platelets <50, 000/mm 3 ) was seen in five patients at T0 and one at T12. Thrombocytopenic patients had statistically significantly higher total BILAG-2004 score at both T0 (BILAG2004: 16.9 (2-53) versus 12 (0-45); p=0.002) and T12 (5.5 (2-15) versus 3.3 (0-16); p=0.04) respectively. TCP at T0 was statistically significantly associated with presence of active haematological involvement at T0, (BILAG2004 category A or B, n=14/27) compared to patients without TCP (n=35/128, p=0.03). Analysis of laboratory markers of disease activity demonstrated statistically significant lower complement 3 levels in thrombocytopenic patients ((0.6mg/L (0.2-1.3) versus 0.8mg/L (0.2-2.0); p=0.005) but not with ESR, anti-dsDNA or immunoglobulins. Haemoglobin, white cell, neutrophil and lymphocyte counts were not statistically significantly associated with thrombocytopenia (p>0.05). Disease-related damage accrual, measured by the SLE International Collaborative Clinic (SLICC) score, showed no statistically significant difference in those with or without TCP (SLICC score 0.3 (0-4) versus 0.14 (0-4); p=0.90) after a median follow-up time of 3.8 (0.9-13.2) years. Conclusions: Almost one in five JSLE patients in this national JSLE Cohort had thrombocytopenia at presentation, most resolving by T12. These patients had significantly higher disease activity scores at diagnosis and at follow up. Thrombocytopenia strongly correlated to complement 3 levels but not with other markers of disease activity or damage accrued to date. On going follow up of this national cohort is taking place. References: Fernández M et al.Arthritis & Rheumatism 2007:56(2);614-621. Carreño L et al. Lupus 1999:8(4);287-292. Sultan SM Rheumatology 2003:42(2);230-234 Disclosure of Interest: None Declared